1999
DOI: 10.1007/s001250051121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of masoprocol on carbohydrate and lipid metabolism in a rat model of Type II diabetes

Abstract: Summary Extracts of the creosote bush (Larrea tridentata, family Zygophyllaceae) have long been used as a folk remedy for Type II (non-insulin-dependent) diabetes by native Americans in southwestern North America. In this study we have evaluated the metabolic effects of masoprocol, a pure compound isolated from the creosote bush, in a rat model of Type II diabetes. Animals were fed a 20 % fat (by weight) diet for 2 weeks prior to intravenous injection with streptozotocin (STZ, 0.19 mmol/kg). Diabetic animals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 21 publications
4
33
0
Order By: Relevance
“…59 It significantly reduces plasma glucose and triglyceride concentrations in rats. 59,60 It also suppresses A␤-induced accumulation of reactive oxygen species. 61 In a recent study 26 of A␤ fibril formation in vitro, NDGA inhibited oligomerization but did not affect fibrillization, which was contrary to the present results.…”
Section: Phenolic Compounds Prevent Ad Pathology 2561mentioning
confidence: 99%
“…59 It significantly reduces plasma glucose and triglyceride concentrations in rats. 59,60 It also suppresses A␤-induced accumulation of reactive oxygen species. 61 In a recent study 26 of A␤ fibril formation in vitro, NDGA inhibited oligomerization but did not affect fibrillization, which was contrary to the present results.…”
Section: Phenolic Compounds Prevent Ad Pathology 2561mentioning
confidence: 99%
“…46 Incidentally, it was shown that the lipoxygenase encoded by ALOX15 augments the resistance to insulin, whereas its inhibition enhances the action of insulin in rat models of insulin resistance and type 2 diabetes. 77 12 ⁄ 15 lipoxigenase deficient mice are resistant to streptozotocin-induced diabetes. 78 Targeted deletion of ALOX15 also protects non-obese diabetic (NOD) mice from autoimmune diabetes.…”
Section: Leukotriene Metabolism Related Genes Alox15 Fem1a Fem1bmentioning
confidence: 99%
“…Of interest are studies showing that masoprocol, a LO inhibitor, can reduce triglycerides, free fatty acids, and improve insulin action in both fructose-fed and fat-fed rat models of insulin resistance and type 2 diabetes. 82,83 In addition, 12-LO products can downregulate glucose transport in VSMC. 84 To further evaluate the effect of insulin resistance on vascular injury responses and 12/15-LO expression, we studied the effect of carotid balloon injury in lean and obese insulin-resistant Zucker rats.…”
Section: The Cyclooxygenase and Lipoxygenase Pathwaysmentioning
confidence: 99%